Translation as a Spatial Process: The Linguistic Landscape of Caroline Bergvall’s Soundworks and Installations - Lacasta Millera, Sofía (Text Matters: A Journal of Literature, Theory and Culture, 2025)
In a constantly evolving, interconnected world, both urban and rural space has become a symbolic site of linguistic and cultural gathering. Thus, translation implies a spatial dimension in which different voices converge to represent a plural, heterogeneous world. Among experimental artist Caroline Bergvall’s interlinguistic and multimodal soundworks, the installation VIA (48 Dante Variations) and the performance Ragadawn highlight the importance of the migration of languages through creative exchange. In this case study, through works that invite a real and figurative journey through language(s), sounds, silence, noise, discourses, and history, I engage with the latest trends in Translation Studies to conceive space as a semiotic landscape that communicates beyond linguistic boundaries. Translating these multimodal works also entails translating a multilingual setting in a creative way, conceiving the environment as a palimpsest (to be) translated, and highlighting the figure of the translator as a cultural agent.